How Much of Hazardous Blue Light is Transmitted By Spectacle Lenses? - Rahmani, Saeed; Nazari, Mohammadreza; Akbarzadeh Baghban, Alireza; Ghassemi-Broumand, Mohammad (Journal of Ophthalmic and Vision Research, 2020)
This is a Letter to the Editor and does not have an abstract.